PENDAMPINGAN KEGIATAN KEAGAMAAN DI MASJID AL FALAH DUSUN KRAJAN DESA SILIRAGUNG KECAMATAN SILIRAGUNG BANYUWANGI - Moh. As'adi; Ahmad Izza Muttaqin (ABDI KAMI: Jurnal Pengabdian Kepada Masyarakat, 2019)
Program of devotion aimed at improving religious activities and the quality of education of the community around the mosque. The Program of devotion that has a direct effort to the community in order to realize the quality of public education. Implementation of KKN in Hamlet Krajan Siliragung subdistrict Siliragung minute well and has been quite successful according to the original purpose. It is undeniable that in its execution, KKN in Krajan's Hamlet experienced various obstacles. However, with the high fighting spirit from the participants of KKN, the active role of the KKN group in public activities and support from the citizens, all these obstacles can be addressed properly. The Program is the result of observations based on data and meetings in the form of KKN group with the head of village, chairman of Ta'mir Masjid Al Falah and the entire society.